Comparative Dosimetric Analysis and Normal Tissue Complication Probability Modelling of Four-Dimensional Computed Tomography Planning Scans Within the UK NeoSCOPE Trial. Issue 12 (December 2020) - Nicholas, O.; Bowden, C.; Selby, A.; Bodger, O.; Lewis, P.; Webster, R.; Radhakrishna, G.; Jones, G.; Hawkins, M.; Mukherjee, S.; Crosby, T.; Gwynne, S.
Abstract: Aims: NeoSCOPE is a trial of two different neoadjuvant chemoradiotherapy regimens for resectable oesophageal cancer and was the first multicentre trial in the UK to incorporate four-dimensional computed tomography (4D-CT) into radiotherapy planning. Despite 4D-CT being increasingly accepted as a standard of care for lower third and junctional oesophageal tumours, there is limited evidence of its benefit over standard three-dimensional computed tomography (3D-CT). Materials: Using NeoSCOPE 4D-CT cases, we undertook a dosimetric comparison study of 3D-CT versus 4D-CT plans comparing target volume coverage and dose to organs at risk. We used established normal tissue complication probability models to evaluate the potential toxicity reduction of using 4D-CT plans in oesophageal cancer. Results: 4D-CT resulted in a smaller median absolute PTV volume and lower dose levels for all reported constraints with comparable target volume coverage. NTCP modelling suggests a significant relative risk reduction of cardiac and pulmonary toxicity endpoints with 4D-CT. Conclusion: Our work shows that incorporating 4D-CT into treatment planning may significantly reduce the toxicity burden from this treatment. Highlights: Dosimetric comparison study of 4D-CT vs 3D-CT using lower oesophageal cancer cases from the NeoSCOPE trial. Integral dose and volume of PTV is significantly reduced with 4D-CT. 4D-CT plans result in significantly lower doses to critical organs at risk. NTCP modelling suggests significant relative risk reduction in cardiac and pulmonary toxicities with 4D-CT.